Design, construction and commissioning of the Braunschweig Icing Wind Tunnel - Bansmer, Stephan E.; Baumert, Arne; Sattler, Stephan; Knop, Inken; Leroy, Delphine; Schwarzenboeck, Alfons; Jurkat-Witschas, Tina; Voigt, Christiane; Pervier, Hugo; Esposito, Biagio (European Geosciences Union (EGU), 2018)
Beyond its physical importance in both fundamental and climate research, atmospheric icing is considered as a severe operational condition in many engineering applications like aviation, electrical power transmission and wind-energy production. To reproduce such icing conditions in a laboratory environment, icing wind tunnels are frequently used. In this paper, a comprehensive overview on the design, construction and commissioning of the Braunschweig Icing Wind Tunnel is given. The tunnel features a test section of 0.5 m  ×  0.5 m with peak velocities of up to 40 m s−1. The static air temperature ranges from −25 to +30 °C. Supercooled droplet icing with liquid water contents up to 3 g m−3 can be reproduced. The unique aspect of this facility is the combination of an icing tunnel with a cloud chamber system for making ice particles. These ice particles are more realistic in shape and density than those usually used for mixed phase and ice crystal icing experiments. Ice water contents up to 20 g m−3 can be generated. We further show how current state-of-the-art measurement techniques for particle sizing are performed on ice particles. The data are compared to those of in-flight measurements in mesoscale convective cloud systems in tropical regions. Finally, some applications of the icing wind tunnel are presented.